Automatic measuring system for acoustical devices calibration in the free-field - Wszołek, G.; Barwicz, W.; Duminov, S. (Archives of Acoustics, 2006)
In connection with the introduction of the new standard PN-EN 61672-2:2005 concerning pattern evaluation tests of sound level meters, which requires performing very large number of measurements to determine the frequency and directional responses, the necessity of developing the new, fully automatic, test system arose. The hitherto applied measuring system was replaced with the automatic one, based on the computer software PomAk. While testing the new method several calibrations of microphones and sound level meters were made. The results were fully satisfying both in their accuracy and in the shortening of the operation time. The capabilities of the software, the calibration results and their verifications are presented in the paper.